Promotora intervention for metabolic and mental health to reduce type 2 diabetes risk: a pilot randomized controlled trial - Maria C. Vargas; Joshua B. Katz; Azucena Lopez; Arturo Carrillo; Dyanna L. Gregory; Matthew J. O’Brien (Scientific Reports)
Abstract The objective of this study was to develop and evaluate a novel behavioral intervention (PRIME2) that integrates evidence-based approaches for reducing diabetes risk and perceived stress. We conducted a pilot randomized controlled trial of the 16-session PRIME2 intervention vs. usual care among 40 Spanish-speaking Latinx adults with prediabetes and body mass index (BMI) ≥ 25 kg/m2. The 3-month change in weight and perceived stress were co-primary outcomes. Secondary outcomes were 3-month changes in hemoglobin A1c (HbA1c), blood pressure, and depressive symptoms. Study participants were women (95%) with mean age 49.9 (± 9.3) years, moderate levels of perceived stress, and risk factors for diabetes, including mean BMI 33.3 (± 5.4) kg/m2 and elevated HbA1c [mean 6.0% (± 0.2)]. PRIME2 participants demonstrated significantly greater 3-month weight loss relative to usual care (− 3.7lbs, p = 0.02). Reductions in perceived stress in both study arms were similar. There were no significant differences in secondary outcomes among PRIME2 participants vs. usual care. This pilot trial demonstrates the feasibility and preliminary weight loss effectiveness of the novel PRIME2 intervention, without observing a significant difference in perceived stress between study arms. Future research should include larger randomized samples that enable a definitive evaluation of intervention effects on both metabolic and mental health endpoints.